Sports-Teachers’ Coaching Style, Behavior, Competency and Student-Athletes Performance in Sports - Rayvin Domingo Pestano (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
Student-athletes’ performance in sports can be influenced by a lot of factors. The coaching style, behavior, and competency of coaches are critical to the development of athletic talent. Thus, this research examined the relationship that existed between coaching style, behavior, competency of coaches, and student-athletes’ performance in sports. Furthermore, predictors of student-athletes’ performance were also explored. Using descriptive correlational research design, quantitative data were gathered using a questionnaire as the main instrument. The study enlisted a total of 59 purposively selected sport-teachers assigned to coach student-athletes. Results of the study revealed that command style, reciprocal style, problem-solving style, and guided discovery style were the coaching styles highly practiced by the respondents. Coaching behavior such as physical training and planning, technical skill, mental preparation, competition strategy, personal rapport, and negative personal rapport was the coaching behavior that is highly applied by the respondents. Coaching competence like motivation, game strategy, character building, and technique were found to be very high. On the other hand, student-athletes performance in sports in the division level was found to be satisfactory, while it is unsatisfactory in regional and national level. Guided discovery coaching style, competition strategy competency, and motivation competency were found to have a moderate significant relationship with student-athletes performance. Competition strategy competency was found to be a predictor of student-athletes performance. Therefore, it is highly recommended that coaches must consistently sustain their high level of competence in this area.